Technical change in Northern Ireland manufacturing 1950-1968 - comment - Glass, J.C. (Economic & Social Studies, 1975)
Recently in this Review, McCulIough (1974) has presented a useful and interesting analysis of technical change in Northern Ireland manufacturing during the period 1950-1968. A major part of his analysis consisted of estimation of the Cobb-Douglas production function, adjusted to permit measurementof both disembodied and embodied technical change. However, as noted by McCulIough, a well-known shortcoming of such an analysis is the assumptions o f unitary elasticity of substitution between capital and labour, and only neutral technical change taking place. The object of this comment is to briefly report some problems encountered in attempting to relax these two assumptions.
Keywords: Manufacturing industry - Northern Ireland; Capital and labour - Northern Ireland